EKSPLORASI KONSEP MATEMATIKA DALAM FIKIH THAHARAH MADZHAB IMAM SYAFI’I - Kukuh Imaduddin; Agung Hartoyo; Asep Nursangaji (Universitas Tanjungpura, 2021)
AbstractAmong the goals of national education is to develop the potential of students to become human beings who believe and fear God Almighty and have noble character. Talking about believing and being obedient to God Almighty and having a noble character, it is very relevant to relate this to religion. This is because every religion requires its adherents to become human beings who are righteous and have noble character in their own ways. Therefore, religious education should be combined with learning activities, especially mathematics learning. There is a close relationship between the religious sciences of mathematics. This study aims to describe the mathematical concepts contained in the fiqh thaharah from Imam Shafi'i school. This research is included in qualitative research. The form of this research is literature study research. The data source in this study is the book Safinatun Najah written by Syekh Salim bin Samir Al-Hadhrami. The data analysis in this study used Miles and Huberman's model and combined it with a scientific approach. The results of this study were found several mathematical concepts contained in the fiqh thaharah from Imam Shafi'i school, namely set, logic, inequality, conversion, geometrid and natural numbers.Keywords: exploration, mathematic concept, Imam Shafi'i school